What Drives Differences in Inequality Across Countries? - Miguel Székely; Marianne Hilgert (Inter-American Development Bank, Research Department, 2000)
This paper presents microeconomic simulation techniques to examine what drives differences in inequality across countries. The simulation decomposes cross-country inequality differences into the importance of individual decisions, such as fertility, mating, labor force participation, and household structure, while at the same time including information on the importance of different income sources. The decomposition is applied to household survey data from 35 countries from 6 regions in the world. The empirical results provide insights into the transmission mechanisms through which inequality is generated.
Keywords: 330; Einkommensverteilung; Dekompositionsverfahren; Fertilität; Erwerbstätigkeit; Familie; Vergleich; Welt